Manual of definitive surgical trauma care - Boffard, Kenneth D. (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Developed for the International Association for Trauma Surgery and Intensive Care (IATSIC), the Manual of Definitive Surgical Trauma Care 5eis ideal for training all surgeons who encounter major surgical trauma on an infrequent basis. This fifth edition had been revised and updated on the basis of new evidence-based information. The increasing role of non-operative management (NOM) has been recognised. With the increased need for humanitarian intervention, as well as military peacekeeping,the Military Module has been substantially updated and broadened to reflect recent conflict experience, and a new expanded section highlighting trauma management under austere conditions has been added.Written by faculty who teach the DSTC Course, this book focuses on life-saving surgical techniques to use in challenging and unfamiliar incidents of trauma.
OCLC-licensed vendor bibliographic record.
Keywords: Surgical emergencies; Traumatology; Wounds and injuries -- Surgery; MEDICAL / Surgery / General